Assessment of Technical Difficulty and Complications of Urological Laparoscopic Operations According to “European Scoring System”: 228 Cases - Fuat Demirel; Fatih Yalçınkaya; Murat Çakan (Journal of Urological Surgery)
Objective Standardization is important for the assessment of technical difficulty and complications in laparoscopic urology surgery. In this study, our laparoscopic operations and complications were evaluated retrospectively by using the European Scoring System and Clavien classification system. Materials and Methods We evaluated a total of 228 laparoscopic urologiy procedures performed between 2002 and 2007. The first 114 cases were named as group 1 and the second 114 cases as group 2. Both of the groups were classified regarding technical difficulty according to the European Scoring System. Complications were divided into two groups: major and minor. Postoperative complications were evaluated by the Clavien classification system. Results The rate of difficult operations was 24.5% and 56.1% in group 1 and group 2, respectively. In group 1, major and total complications were more common in difficult operations than in easy operations (p=0.045, p=0.006). Minor complications were similar (p=0.064). In group 2, complication rates were similar for both difficult and easy operations. (p=0.694, p=0.509, p=0.273). Complication rates per case was 0.21 (0-3) in group 1 and 0.19 (0-3) in group 2 and there was no significant difference between the two groups (p=0.790). Postoperative complications were classified using the Clavien classification system. 17% (n=4/23) of 23 complication was grade 1, 48% (n=ll/23) was grade 2, 26% (n=6/23) was grade 3a, 9% (n=2/23) was grade 3b. There were no grade 4 and 5 complications. 3% of the cases were converted to open surgery and no statistically difference was found between the groups (p=0.446). Conclusion We assume that the European Scoring System and the Clavien classification system are important in the assessment of difficulty of the cases and standardization of the analysis of postoperative complications.